Schizophrenia Polygenic Risk and Brain Structural Changes in Methamphetamine-Associated Psychosis in a South African Population - Passchier, Ruth V.; Stein, Dan J.; Uhlmann, Anne; van der Merwe, Celia; Dalvie, Shareefa (Frontiers in Genetics, 2020)
Background: The genetic architecture of psychotic disorders is complex, with hundreds of genetic risk loci contributing to a polygenic model of disease. Polygenic overlap between psychotic disorders and putative brain endophenotypes has been documented in European, American and Asian ancestry populations, but has not been explored in populations of African ancestry. The aim of the study was to determine the association between polygenic risk scores (PRS), methamphetamine-associated psychosis (MAP) and brain structural changes in individuals from a South African population group. Method: The study sample consisted of three participant groups: 31 individuals with MAP, 49 with methamphetamine dependence without psychosis (MD) and 51 healthy controls (HC). Using PRSice, PRS was derived for each of the participants with GWAS summary statistics from the Psychiatric Genomics Consortium schizophrenia working group. Regression analyses were performed to determine whether there were associations between PRS, MAP diagnosis, and whole brain or regional grey and white matter measures. Results: No significant associations between PRS, MAP diagnosis and brain structural measures were observed, after correction for multiple testing. Although non-significant, an increase in PRS in the MAP group; while a decrease in PRS in the MD and HC groups was observed. Discussion: Although this study was underpowered to reach statistical significance, the positive direction of association between schizophrenia-derived PRS and MAP, is in keeping with previous research, suggesting that individuals who develop psychosis in response to methamphetamine use have a greater genetic risk for psychosis. Larger studies, that include diverse populations, and more nuanced structural and functional brain measures, are required to further investigate the relationship between PRS, brain structural changes and psychosis.